Committee Decision-Making under the Threat of Leaks - Sebastian Fehrler; Volker Hahn (Institute of Labor Economics (IZA), 2020)
Leaks are pervasive in politics. Hence, many committees that nominally operate under secrecy de facto operate under the threat that information might be passed on to outsiders. We study theoretically and experimentally how this possibility affects the behavior of committee members and the decision-making accuracy. Our theoretical analysis generates two major predictions. First, a committee operating under the threat of leaks is equivalent to a formally transparent committee in terms of the probabilities of project implementation as well as welfare (despite differences in individual voting behavior). Second, the threat of leaks causes a committee to recommend rejection of a project whenever precise information has been shared among committee members. As a consequence, a status-quo bias arises. Our laboratory results confirm these predictions despite subjects communicating less strategically than predicted.
Keywords: C92; D71; D82; J45; 330; committee decision-making; strategic communication; voting; leaks; transparency; monetary policy committees; information aggregation